Transitions experienced by people living with limitations resulting from leprosy: a research-care study - Rayla Maria Pontes Guimarães Costa; Marcia Astrês Fernandes; Ivete Palmira Sanson Zagonel (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: to understand the transitional processes that affect the adaptation of people who live with limitations resulting from leprosy. Methods: This is a qualitative study based on the precepts of Transition Theory, mediated by care-research, with 24 people with limitations resulting from leprosy in an ex-hospital colony in Piauí. Semi-structured interviews were carried out. The interviews were analyzed using Iramuteq software. Results: the researched-caregivers experienced the four types of transitions, including feelings of fear, worry, loneliness, hopelessness, guilt and a tendency to hide the diagnosis. Breakdowns and resignation were revealed, with spirituality, adaptation to the new life situation and acceptance as facilitating conditions for coping with the transitional process, with a consequent improvement in quality of life. Final considerations: the transitional processes had a positive significance, since they contributed to adaptation and the achievement of quality of life.